MATHEMATICAL DISPOSITION ANALYSIS OF ELEMENTARY SCHOOL STUDENTS ON THEIR MATHEMATICAL PROBLEM-SOLVING SKILL - Riandi Marisa; Yulia Santi; Ety Mukhlesi Yeni; Sri Dewi Nirmala (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The role of students' attitudes (disposition) towards mathematics is an important element in solving their mathematical problems and must be maximized properly. Disposition has the following indicators such as self-confidence, flexibility, persistence, curiosity, reflecting, and applying it. This paper describes the elementary students' mathematical disposition profile toward their problem-solving skills. The research method uses qualitative-descriptive. Data were collected through questionnaires, observations, and interviews, which were subsequently analyzed by triangulation technique. The results indicate that there is a significant relationship between elementary school students' mathematical dispositions and their problem-solving skills. Students who achieve the